2014
DOI: 10.1186/1477-7819-12-120
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone receptor status in breast cancer: a cross-sectional study of 450 women in Kerala, South India

Abstract: BackgroundHormone receptor status is an important prognostic and therapeutic tool in breast cancer. The objectives of our study were to create a database of breast cancer patients in Central Kerala between January 2010 and December 2012 and analyze the proportions of estrogen receptor and progesterone receptor positivity in premenopausal and postmenopausal women with breast cancer.MethodsEstrogen and progesterone receptor status were evaluated by immunohistochemistry. The chi-square test was used for statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
4
13
1
1
Order By: Relevance
“…[23] The average ER positivity for white women in the US is 77%. PR positivity from our study in female breast cancer cases is 45% which is close to percentage of ER value and comparable to other studies reported from different parts of India with PR expression of 33.3%, [24] 41.5%, [25] and 42%. [26] Though white women in US showed 55% PR positivity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[23] The average ER positivity for white women in the US is 77%. PR positivity from our study in female breast cancer cases is 45% which is close to percentage of ER value and comparable to other studies reported from different parts of India with PR expression of 33.3%, [24] 41.5%, [25] and 42%. [26] Though white women in US showed 55% PR positivity.…”
Section: Discussionsupporting
confidence: 78%
“…Most other studies have found 51 -60 years as the second most common decade for breast cancer. [19] In our study, the overall ER positivity in female breast cancer cases is found to be 44.0%, which lies in the range reported by different Indian institutes, however, pretty low as compared to the reportings form western world. [20] ER negative and PR positive tumours are relatively rare cancers based on hormone receptor expression which accounts for just 1-4% [21] of all cases according to Navani et al and was found to be 5.3% [22] in the study of Vettuparambil et al Studies done in India and on Indian emigrants have found ER positivity in Indian women in the range of 34.5% to 55.1%.…”
Section: Discussionmentioning
confidence: 72%
“…[ 8 ] There is an annual rise of 0.5%–2% in the incidence across all regions of India and this rise is even more in younger females less than 45 years. [ 9 ] Most Indian studies to date have shown median ages ranging from 48-53 years. [ 7 8 9 10 11 ] In our study as well, the median age was 48 years, reinforcing the fact that breast cancer in Indian women occurs at least a decade younger than those in the West.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Most Indian studies to date have shown median ages ranging from 48-53 years. [ 7 8 9 10 11 ] In our study as well, the median age was 48 years, reinforcing the fact that breast cancer in Indian women occurs at least a decade younger than those in the West. [ 12 ] Most western data show a median age around 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ER and PR expression has been found similar in some Indian studies but in western literature studies have found much higher prevalence as compared to the studies in India. [6][7][8][9] This difference could be because of different genetic pool and ethnic differences. We found about 9.6% of cases being triple negative for receptors in our study population.…”
Section: Discussionmentioning
confidence: 99%